The management of pregnancy and delivery in 3‐hydroxy‐3‐methylglutaryl‐CoA lyase deficiency. Issue 6 (21st March 2016) - Pipitone, Angela; Raval, Donna B.; Duis, Jessica; Vernon, Hilary; Martin, Regina; Hamosh, Ada; Valle, David; Gunay‐Aygun, Meral
Abstract : 3‐hydroxy‐3‐methylglutaric (HMG)‐CoA lyase is required for ketogenesis and leucine degradation. Patients with HMG‐CoA lyase deficiency typically present with hypoketotic hypoglycemia and metabolic acidosis, which can be fatal if untreated. The patient is a 28‐year‐old female with HMG‐CoA lyase deficiency who presented at 4 weeks gestation for prenatal care. Protein intake as well as carnitine supplementation were gradually increased to support maternal and fetal demands up to 65 g per day for protein and 80 mg/kg/day for carnitine. Fetal growth was appropriate. At 36 5/7 weeks, she presented with spontaneous rupture of membranes. Twice maintenance 10% glucose‐containing intravenous fluids were initiated. During labor, vomiting and metabolic acidosis developed. Delivery was by cesarean. Preeclampsia developed postpartum. The patient recovered well and was discharged home on postpartum day 5. Stress of pregnancy and labor and delivery can lead to metabolic decompensation in HMG‐CoA lyase deficiency. Patients should be monitored closely by a biochemical geneticist, dietitian, and high‐risk obstetrician at a tertiary care center during their pregnancy. Fasting should be avoided. Intravenous 10% glucose‐containing fluids should be provided to prevent catabolism and metabolic decompensation during labor and delivery. © 2016 Wiley Periodicals, Inc.